EFFECTS OF DIFFERENT LEVELS OF FORAGE AND CONCENTRATE ON THE METABOLISM OF GLUCOSE, β-HYDROXYBUTYRATE AND NONESTERIFIED FATTY ACID IN LIVERS OF NONLACTATING GOATS - S. Zhuang; R. Yan; W.C. Dong; T. Zhang G.J. Chang; X. Z. Shen (Journal of Animal and Plant Sciences, 2014)
The aim of this study was to investigate the effects of different levels of forage and concentrates diets on the metabolism of glucose, β-hydroxybutyrate (BOHB) and nonesterified fatty acid (NEFA) in livers of nonlactating goats. Six catheterized GuanZhong goats (40±2 kg weight) were fed high concentrate diet (HC, 40% hay, 60% concentrate) or high forage diets (HF, 60% hay, 40% concentrate). Blood samples were simultaneously taken from the portal, hepatic and arterial catheters at 0 h, before feeding, 2, 4, 6 and 8 h after feeding. The HC fed goats exhibited higher (P<0.01) plasma glucose concentration and arterial flow accompanied by NEFA, BOHB(P<0.01) and hepatic glucagons concentrations (P<0.10) while NEFA portal flow and BOHB hepatic flow decreased (P<0.05). Glucose portal-arterial concentration difference and hepatic-portal concentration differences in BOHB and NEFA tended to decreased (P<0.10) with increasing NEFA portal and hepatic arterial concentration differences (P<0.05) in HC fed goats. There were no differences in net flow of glucose, BOHB and NEFA across splanchnic tissues, but a decreased net portal absorption in NEFA (P<0.05) accompanied with a tendency for depressing its net PDV plus hepatic uptake (P<0.10). In conclusion, the high concentrates diet may increase hepatic gluconeogenesis in nonlactating goats.
Keywords: Concentrate; Liver; Glucose; Nonesterified fatty acid; β-Hydroxybutyrate; Goat